Optimal control of high-power density hybrid electric vehicle charger. (November 2021) - Hassan, Tehzeeb-ul; Cheema, Khalid Mehmood; Mehmood, Kashif; Tahir, Muhammad Faizan; Milyani, Ahmad H.; Akhtar, Muhammad
Abstract: This research utilizes a hybrid technology through resonant line-level control phase-shifted full-bridge (HR-LLC-PSFB) dc–dc converter. In this research, a line level control (LLC) auxiliary circuit is used to achieve zero-current soft-switching turned-off operation of a controlled switch. The zero-voltage soft-switching turned-on operation is achieved by using the transformers' magnetic branch energy and the energy reflected by the output filter inductor. The effective turn's ratio of the isolating transformers is used to reduce the inverter circuit's voltage stresses. The effect of voltage overshoots and freewheeling circulating current in rectifying branches is improved by implementing an energy recovery circuit with an output filter. A closed loop coordination proportional integral derivative (PID) controller is proposed to generate the pulse width modulation (PWM) control signal to transmit smooth power by controlling output voltage and current values. The droop constant current charging (CCC) and reduced constant current charging (RCCC) technique is proposed for the charging process. Simulations performed in MATLAB and results substantiate the proposed work superiority in comparison to other topologies.